2023
DOI: 10.3389/fimmu.2023.1125658
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping cytokines in H. pylori infection and gastric cancer: A tandem meta-analysis

Abstract: BackgroundPrevious evidence indicated that Helicobacter pylori-induced inflammation is the first step towards gastric carcinogenesis. However, investigations of the immunological factors driving this process have shown inconsistencies. We aimed to present a thorough summary of all researched cytokines in relation to H. pylori infection and GC and relate these to global GC risk.MethodsWe performed a systematic review and tandem meta-analysis identifying all published studies reporting on serum cytokine levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The mechanism behind H. pylori -associated inflammation and GC development remains incompletely understood, and identifying factors that could contribute to these processes remains important. A previous meta-analysis identified IL-6 as a potential key factor in this process [11] , making it a subject for further investigation. We aimed to explore the role of IL-6 in H. pylori -associated gastric cancer and show that macrophages and epithelial cells demonstrate both autocrine and paracrine IL-6 induction, which is enhanced by H. pylori .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism behind H. pylori -associated inflammation and GC development remains incompletely understood, and identifying factors that could contribute to these processes remains important. A previous meta-analysis identified IL-6 as a potential key factor in this process [11] , making it a subject for further investigation. We aimed to explore the role of IL-6 in H. pylori -associated gastric cancer and show that macrophages and epithelial cells demonstrate both autocrine and paracrine IL-6 induction, which is enhanced by H. pylori .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence indicate that the pro-inflammatory cytokine interleukin-6 (IL-6) is a crucial factor in gastric carcinogenesis [6] , [7] , [8] , [9] , [10] . Previous studies showed a substantial and relevant association between the systemic IL-6 levels induced by H. pylori -infection and the relative incidence of GC [11] . IL-6 serum levels are increased in GC patients, and are associated with disease progression and worse prognosis [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 96%
“…In immune cells at the site of infection, the expression of proinflammatory cytokines and the chemokine CCL5 increases, key in the development of chronic gastric inflammation and the onset of GC ( 23 ). In a meta-analysis study of the literature, a significant increase in circulating levels of IL-6 and TNF-a was found during infection with the bacteria, when it was also associated with GC, increased serum levels of IL-6 IL-7, IL-10, IL-12 and TNF-a were found ( 24 ). Another study demonstrated that the presence of the bacteria favors the activation of nuclear factor kappa B (NF-kB) in gastric epithelial cells, generating the release of inflammatory mediators such as interleukin-8 (IL-8) ( 25 ).…”
Section: Gc and Inflammationmentioning
confidence: 99%
“…Gastric cancer, also known as stomach cancer, is a relatively common malignancy, being the third most common cause of cancer-related deaths worldwide (Lu et al 2022 ; Ma et al 2022 ). With a relative five-year survival rate below 30% in its advanced stage, it has a poor prognosis and represents a substantial socio-medical burden that remains to be addressed (Yu et al 2023 ). Research on the disease has linked numerous non-coding RNAs to its onset and malignant spread.…”
Section: Introductionmentioning
confidence: 99%